Women's mental health and resilience in the perinatal period and five years after first-time motherhood: a mixed methods study - Hannon, Susan Elizabeth (Trinity College Dublin. School of Nursing & Midwifery. Discipline of Nursing, 2024)
Background: Although motherhood is associated with joy and celebration, adverse mental health outcomes are widely documented in international literature. Yet, publications concerning maternal mental health in an Irish context are sparse and incongruous. Additionally, both Irish and international literature most often take a pathology focused approach and concentrate on the perinatal period, with less attention to mental health and well-being through the motherhood journey. Design: A multistage mixed-methods design. Aim: The research aimed to identify the prevalence and change of first-time mothers’ mental health symptoms in the perinatal period, and their mental health symptoms and well-being five years after first-time motherhood. Additionally, the research aimed to develop a deeper understanding of resilience in a maternal context through exploration of women’s views on, and experience of, mental health and resilience in the motherhood transition. Setting: Three maternity hospitals in the Republic of Ireland. Sample: Fourteen women took part in the participatory research component of phase 1; twenty-three women took part in the in-depth interviews of phase 2. Samples sizes for analysis of the quantitative data of phase 3 were defined by survey completion. Perinatal data analysis comprised 2380 participants and five-year follow-up analysis comprised 1155 participants. Methods: This study used a multistage mixed-methods design combining explanatory-sequential and convergent approaches, with a participatory research component. Three phases of research were embedded within the longitudinal MAMMI study. Phase 1 consisted of two steps; the first entailed conducting a concept analysis of the concept of resilience within the context of the perinatal period and early motherhood. The second step involved presenting the findings of the concept analysis to fourteen mothers to ascertain their perspectives on the literature, and operationalise their feedback to inform the subsequent phases of the research. Phase 2 consisted of in-depth interviews with twenty-three mothers to develop a detailed understanding of women’s life-course experiences of mental health, and the processes involved in navigating to and negotiating for mental health and well-being. Phase 3 involved analyses of quantitative mental health symptomatology and socio-demographic data collected during pregnancy and at four intervals in the first year postpartum (perinatal data). Additionally, phase 3 involved analyses of mental health symptomatology, mental well-being, socio-demographic, and emotional and relational data at five years after first-time motherhood (five-year follow-up data). Findings: Phase 1: Concept analysis and women’s views: The concept analysis found that resilience literature in the area of maternal mental health often adopted trait-based conceptualisations; whereas women viewed resilience as influenced by multi-systemic processes. Linguistically, ‘coping’, ‘adaption’, ‘resistance’ and ‘protection’ were words associated with resilience in the included literature. Some women voiced negative connotations around the term ‘coping’ in relation to motherhood. Analysis of the logical principle illustrated that illness absence was frequently, though not exclusively, equated to resilience. However, women were resistant to this conceptualisation and suggested alternatives in relation to well-being and functioning. Pragmatic application of resilience research was not well developed within the literature, and women expressed wariness that research may be used to reduce or remove practical and mental health supports for mothers and families. Phase 2: In-depth qualitative interviews: How women navigate to, and negotiate for, what they need for their mental health and well-being in motherhood underpinned the qualitative data analysis, where navigation and negotiation were understood to underlie the processes of resilience. Thematic analysis generated seven themes and ten sub-themes. Before navigating towards the needs that sustain their own well-being, mothers must first negotiate with internalised social and cultural narratives of the ideal mother. Internalised narratives were reinforced by deficits in policy and services, which conveyed society’s unrealistic expectations of mothers. Mothers negotiated to establish an equal partnership of mutual responsibility for parenting with their parent-partner in motherhood, which had implications for their career development, maintaining social relationships, and managing multiple roles and responsibilities. Motherhood introduced social isolation, which required efforts to navigate towards building new social supports. Mothers who sought professional resources had to navigate and negotiate gaps in mental healthcare service provision; gaps that were typified by narrow gateways to accessing care, and narrow pathways of treatment options. Phase 3: Quantitative data analysis: Perinatal data: The prevalence for depression, anxiety and stress was 14.2%, 9.5%, and 19.2% respectively. Depression and stress were lowest in pregnancy and higher in the postpartum, anxiety was relatively constant through the perinatal period. Comorbid anxiety/depression (CAD) prevalence was 1.5% in pregnancy and almost 2% in the postpartum year. Younger maternal age, being single/not living with a partner, not having a postgraduate education and being unemployed during pregnancy were associated with higher odds of reporting symptoms of depression, anxiety, stress and CAD in the postpartum year. Being born in a non-EU country was associated with higher odds of reporting anxiety, pre-term birth with higher odds of reporting depression, and caesarean birth with higher odds of reporting depression and stress. Experiencing mental health problems in the year prior to pregnancy were associated with increased odds of reporting depression, anxiety, and stress in the postpartum year. Experiencing mental health problems, relationship problems or fear of a partner during pregnancy were associated with increased odds of reporting depression, anxiety and stress. Increased reports of mental health symptoms were associated with reporting a higher number of physical health problems. Five-year follow-up data: The prevalence for depression, anxiety and stress was 11.2%, 12.6%, and 14.2%, respectively. Prevalence of flourishing mental health was 60.4%. Younger maternal age and not obtaining a postgraduate education before index pregnancy were associated with increased odds of depressive, anxiety and stress symptoms at five-year follow-up. Postgraduate education attainment was associated with increased odds of flourishing mental well-being reports at five-year follow-up. Women who completed the five-year data collection after the introduction of Covid-19 health restrictions were more likely to report depressive, anxiety and stress symptoms. Women who had one child at five-year follow-up were also less likely to have a partner or postgraduate education, and had higher odds of reporting depressive symptoms. Having a lesser number of practical social supports, less practical and emotional partner support, and infrequent personal time were associated with reports of depression, anxiety and stress. While increased frequency of personal time was associated with increased odds of flourishing mental health. Dissatisfaction with a partner’s contribution to household tasks, childcare or the parenting role, and negative perception of emotional support and relationship satisfaction were associated with increased symptomatology reports and decreased flourishing. Conclusion: Substantial proportions of mothers experience physical and mental health symptoms throughout the first year postpartum, and reports of mental health symptoms increase at five-year follow-up. Women with less socio-economic resources are at increased risk of reporting clinically significant symptoms. Women who experience mental health problems beyond current maternity care service provision are not supported by a system that is enabled to readily detect and offer treatment. Rather, women must self-identify if they require assistance. Additionally, women in the perinatal period and at five-year follow-up must navigate and negotiate with disjoined, confusing, and costly service and care pathways to seek treatment.
APPROVED
Keywords: Resilience; Perinatal Mental Health; Maternal Mental Health; Mental Health and Well-being; Motherhood; Quality of Life